EKSPLORASI KREATIVITAS FALINOARY MELALUI PENCIPTAAN KARYA TARI ADAPTSEA: - - Falinoary Pasudiwo; Maharani Luthvinda Dewi (Universitas Hamzanwadi, 2025)
This research aims to describe the form and creative process of the dance work Adaptsea, created by Falinoary Pasudiwo in 2025 and performed at the Main Theater Building of the Indonesian Institute of the Arts Surakarta. To analyze the creative process, this study applies the 3R theory by Eko Supriyanto, which involves the stages of Re-Visiting, Re-Questioning, and Re-Interpreting, as well as the theory of Alma M. Hawkins in her book Creating Through Dance, which supports the exploration, improvisation, and composition process. Meanwhile, to address the issue of the dance form, this research utilizes the theory from Sumandiyo Hadi in his book Aspek-Aspek Koreografi Kelompok (Aspects of Group Choreography). This study employs a qualitative approach with data collection techniques including observation, interviews, and literature review. The results indicate that the form of the dance Adaptsea includes elements such as dance movement, dance space, musical accompaniment, dance title, dance theme, dance type, number of dancers, makeup and costume, lighting design, and props. Furthermore, in its creation process, this work successfully constructs an imaginative space for the audience through its main idea, namely the adaptation of coastal communities to tidal flooding disasters.